Preplaced Lightweight Aggregate Concrete (PLWAC) Dengan Bahan Agregat Kasar Batu Apung dan Fly Ash Sebagai Agregat Halus - Adhika Raffi Athallarizq; Ngudiyono; Akmaluddin; Buan Anshari; Hariyadi; Ni Nyoman Kencanawati; Tri Sulistyowati (Institut Teknologi Garut, 2026)
Concrete is a composite material widely used because it has high compressive strength; however, it has a weakness in the form of high density. Lightweight concrete innovation such as Preplaced Lightweight Aggregate Concrete (PLWAC) offers a solution, using a method in which lightweight aggregate is first placed into the mold and then filled with grouting material, which is expected to reduce density. This study uses pumice stone as coarse aggregate and fly ash as fine aggregate. The purpose of this study is to analyze the effect of variations in the cement-to-fly ash ratio on the flowability and compressive strength of the grouting material, as well as to evaluate the mechanical properties (compressive strength, splitting tensile strength, and flexural strength) and physical properties (density and water absorption) of PLWAC. The grouting material used variations of cement-to-fly ash ratios of 1:0.5, 1:1, 1:1.5, and 1:2. The grouting method was carried out using manual pumping into molds that had been filled with pumice aggregate. The specimens consisted of 12 cubes measuring 50 mm × 50 mm × 50 mm for grouting material compressive strength testing, 28 cylinders measuring 150 mm × 150 mm for compressive strength, splitting tensile strength, and absorption tests, and 12 beams measuring 150 mm × 150 mm × 530 mm for PLWAC flexural strength testing. The test results at 56 days show that increasing the fly ash content caused a decrease in mechanical properties. The highest compressive strength of the grouting material was 28.64 MPa at a ratio of 1:0.5. Meanwhile, PLWAC achieved the highest compressive strength of 6.22 MPa, splitting tensile strength of 1.27 MPa, and flexural strength of 1.28 MPa. The lowest PLWAC density was obtained in the cement-to-fly ash composition of 1:2, at 1,388.3 kg/m³, with water absorption of 28.79 percent.